Hěde oḱo hedem ḱaw ya-paǐ-to něs: this day this land/place/time we talk - Jun Sunseri; Matthew Moore; Rebecca Allen (Frontiers in Environmental Archaeology)
Catastrophic fire behavior in the Sierra Nevada range is increasing in tandem with worsening forest conditions related to non-Native approaches to fire ecology and climate change. Among the myriad negative human and community effects linked to thistrend, lesser understood are the relationships between differing forest management strategies and impacts to Ancestral Places or 'Esak 'Tima (Maidu and Nisenan for “places to learn”) which are living locations and traces of Ancestral practices that are integral to the health of Native Californian communities. Tribal Historic Preservation Offices, TEK specialists, and Tribal Leadership are on the front lines of government-to-government negotiations of sovereignty, especially with respect to their communities' living relationships with Ancestral Places. These are sometimes located in places managed by other institutions, agencies, and land occupiers and are most often far more than just dots on a map, but rather complex interconnected landscapes of Ancestral practices. These Tribal perspectives on guarding Ancestral Places are linked to not only the uses of Cultural Fire, or wénném sa in ecosystem restoration but also increasing aspects of the legibility and reincorporation of elements of Ancestral Places and Practices into healthy contemporary relationships with Tribal community members. These aspects of applied Traditional Ecological Knowledge and practice are highlighted in the relationships between wénném sa, Tribal archaeology, and forest management techniques our coalition is researching in California and are part of how our partnership in community-accountable archaeological research supports restorative justice. We foreground the principles of guardianship in the forest to build datasets that will support community priorities for Tribal access, food and medicine sovereignty, and intergenerational knowledge transfer. These kinds of direct action guardianship and mandated research will serve as models for co-management policies in other forests. Central to our efforts is demonstrating a model of evidence-based practice in recognition that leaders in our rapidly changing ecological reality cannot have a complete toolkit without them, especially if societies attempt to reconcile issues of racial just ice and sovereignty. Our partnership in this way connects heritage resource management to forest management and human rights policy while building community accountable research deliverables.